Human Resources for Health: An International Comparison of Health Occupations from Labor Force Survey Data - Neeru Gupta; Khassoum Diallo; Pascal Zurn; Mario R. Dal Poz (Luxembourg Income Study (LIS), 2002)
Human resources are an essential element of a health system's inputs, and yet there is little consistency between countries in how human resource policies and strategies are developed and implemented. The analysis of the impacts of services on population health and well-being attracts more interest than analysis of the situation of the workforce in this area. The objective of this paper was to present an international comparison of the health workforce in terms of skill mix, sociodemographics and other labor force characteristics, in order to establish an evidence base for monitoring and evaluation of human resources for health. Data were drawn from LIS/LES surveys conducted between 1989 and 1997 for 18 countries with developed market and transitional economies. Considerable cross-national variations were observed in terms of the share of the health workforce in the total labor market, with little discernible pattern by geographical region or type of economy. Increases in the share were found among most countries for which time-trend data were available. The evidence further suggested that gender inequity in human resources for health remains an important shortcoming of many health systems. However, unexpected patterns of occupational distribution and educational attainment for selected countries pointed to definitional inconsistencies in the classification of health occupations across surveys.
Keywords: 330; Gesundheitsberufe; Gesundheitswesen; Welt